2017
DOI: 10.1111/1750-3841.13729
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Escherichia coli O157:H7 in Biofilms Using Bacteriophage BPECO 19

Abstract: Biofilm formation is a growing concern in the food industry. Escherichia coli O157:H7 is one of the most important foodborne pathogens that can persists in food and food-related environments and subsequently produce biofilms. The efficacy of bacteriophage BPECO 19 was evaluated against three E. coli O157:H7 strains in biofilms. Biofilms of the three E. coli O157:H7 strains were grown on abiotic (stainless steel, rubber, and minimum biofilm eradication concentration [MBEC ] device) and biotic (lettuce) surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…This sequential treatment provided a reduction of 5.71 log CFU/ cm 2 , quite higher than the ones observed for CNP or the phages alone (about 2 log CFU/cm 2 ) [67]. In 2017, Sadekuzzaman et al [68] reported the treatment of biofilms formed by strains ATCC 43889, NCCP 11090, and NCCP 14541 on different surfaces (stainless steel, rubber, and leaf) at two different temperatures (10 and 30 C), using the lytic phage BPECO 19. After 2-h, phage BPECO 19 was able to reduce bacteria numbers of biofilms formed at both temperatures and on different surfaces, with lower efficacy on the leaf surface.…”
Section: Bacteriophages For Controlling E Coli Populationsmentioning
confidence: 85%
“…This sequential treatment provided a reduction of 5.71 log CFU/ cm 2 , quite higher than the ones observed for CNP or the phages alone (about 2 log CFU/cm 2 ) [67]. In 2017, Sadekuzzaman et al [68] reported the treatment of biofilms formed by strains ATCC 43889, NCCP 11090, and NCCP 14541 on different surfaces (stainless steel, rubber, and leaf) at two different temperatures (10 and 30 C), using the lytic phage BPECO 19. After 2-h, phage BPECO 19 was able to reduce bacteria numbers of biofilms formed at both temperatures and on different surfaces, with lower efficacy on the leaf surface.…”
Section: Bacteriophages For Controlling E Coli Populationsmentioning
confidence: 85%
“…A bacteriophage BPECO 19 was evaluated as possible inhibitor of a three E. coli O157:H7 strain biofilm grown on both abiotic (stainless steel, rubber, and minimum biofilm eradication concentration device) and biotic (lettuce leaves) surfaces. This bacteriophage showed great biofilm inhibition activity on all the tested surfaces, being suggested as effective antibiofilm agent in food industry [101].…”
Section: Fighting Against Biofilms With Bacteriophagesmentioning
confidence: 91%
“…Evaluation of the antimicrobial activity of the phage on fresh food was carried out using a modified method from previous reports [19,48]. Romaine lettuce was purchased from a local grocery store and kept at 4 °C.…”
Section: Evaluation Of the Antimicrobial Effect Of Phage On Fresh Letmentioning
confidence: 99%